Spatial Differences in Emission Reduction Effect of Servitization of Manufacturing Industry Export in China. Issue 8 (21st June 2021) - Li, Xiuzhen; Wang, Xiangjin; Zhang, Yun; Miao, Xiao
ABSTRACT: Manufacturing servitization may reduce energy consumption and achieve low-carbonization of global value chain. We calculated and analyzed carbon emissions embodied in export and manufacturing servitization with China as research object, and found that spatial clustering characteristics of export-embodied carbon emissions and spatial differences in emission reduction effect were significant, and reduction effect of manufacturing servitization on export-embodied carbon emissions in eastern and northeastern China has a stronger role than in other regions. So countries should strengthen coordination of cross-regional inter-industry value chains, and reduce manufacturing emissions by improving servitization.